Interpretation of the Linguistic Sign in Semiotic Analysis: Between Communication and Signification - bougrine, Abu Bakr (El Omda in Linguistics and Discourse Analysis, 2022)
This research paper examines two influential ways in the interpretation of the linguistic sign, namely: the semiotics of communication and the semiotics of semantics, so they meet sometimes, and they converge on others. The semiotics of communication is considered the linguistic sign in the case of achieving reporting (communicative contact), While semantic semiotics acquires its objective framework from those relationships that organize signs within a signifying system.